2017
DOI: 10.11648/j.ajns.20170604.17
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Cancer Care and Oncology Nursing in the Kingdom of Saudi Arabia

Abstract: Abstract:Cancer prevalence is increasing in the Kingdom of Saudi Arabia. While the exact etiology of this trend is unknown, it can perhaps be partially attributed to an increased life expectancy and changes in lifestyle habits. One of the main challenges to the provision of appropriate cancer and palliative care is the critical shortage of oncology healthcare professionals, including nurses. The Kingdom of Saudi Arabia is characterized by its Islamic faith, culture, and unique traditions that may contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Nursing care for terminally ill cancer patients is routinely provided by oncology nurses in Saudi Arabia, as specialist palliative care nursing is in its infancy [6]. As oncology services in rural settings are limited, referrals to metropolitan services may cause delayed diagnosis or treatment, and patients consequently presenting with advanced stage cancer [7]. Further, for cultural reasons, Saudi patients may not disclose their cancer diagnosis or prognosis to their family, which may result in delayed treatment and/or cancer-related risks [7].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Nursing care for terminally ill cancer patients is routinely provided by oncology nurses in Saudi Arabia, as specialist palliative care nursing is in its infancy [6]. As oncology services in rural settings are limited, referrals to metropolitan services may cause delayed diagnosis or treatment, and patients consequently presenting with advanced stage cancer [7]. Further, for cultural reasons, Saudi patients may not disclose their cancer diagnosis or prognosis to their family, which may result in delayed treatment and/or cancer-related risks [7].…”
mentioning
confidence: 99%
“…As oncology services in rural settings are limited, referrals to metropolitan services may cause delayed diagnosis or treatment, and patients consequently presenting with advanced stage cancer [7]. Further, for cultural reasons, Saudi patients may not disclose their cancer diagnosis or prognosis to their family, which may result in delayed treatment and/or cancer-related risks [7]. Although specialised cancer treatment is available for Saudi patients, for reasons specified above, some patients do not seek medical advice except in the late stages of their cancer when the effectiveness of the treatment is minimised, resulting in a high mortality rate and poor prognosis [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although Kim & Kim [ 39 ] used a different scale to measure stress, they found that the dimension related to excessive workload was the most affected, as was in the present study. To be aware of such stress levels is of great importance due to the well-known association of stress with reduced work performance, higher job turnover, decreased job satisfaction, loss of productivity, high rates of absenteeism, and reduced quality of nursing care for patients [ 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Between 1999-2015, the reported cancer cases in SA increased by 136%, expected to rise a further 63% by 2030 (Jazieh et al, 2019). Patients with cancer in SA are at risk of developing serious complications due to inadequate access to cancer care facilities, a shortage of qualified oncology healthcare providers (HCPs), a shortage of cancer treatment, and inadequate resources to support cancer care and prevention (Al-Ahmadi et al, 2013;AlAzmi et al, 2020;Wazqar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%